2018
DOI: 10.1093/ajcp/aqy023
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Cytogenetic Abnormalities in Intravascular Large B-Cell Lymphoma

Abstract: Recurrent cytogenetic abnormalities involving chromosomes 1, 6q, and 18 are present in greater than 50% of ILBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…These findings were similar to the study of Klairmont et al. which showed most of IVLBCL patients were associated with complex karyotypes with recurrent cytogenetic abnormalities commonly involving chromosomes 1, 6q, and 18 [ 39 ]. Early mortality was found in two of these patients in our study, but the remaining one was still alive to the date of last follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…These findings were similar to the study of Klairmont et al. which showed most of IVLBCL patients were associated with complex karyotypes with recurrent cytogenetic abnormalities commonly involving chromosomes 1, 6q, and 18 [ 39 ]. Early mortality was found in two of these patients in our study, but the remaining one was still alive to the date of last follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…Most cases have a complex karyotype. Klairmont et al 42 reported that chromosome 1 is commonly involved in 72% of cases, followed by chromosomes 3, 6q, 14 and 18. Gene mutation analysis has shown mutations in PIM1 (67%), MYD88 (44-59%), CD79b (26-67%), PRDM1 (44%), BTG2 (22%) and EZH2 (4%).…”
Section: Immunophenotypementioning
confidence: 99%
“…Gene mutation analysis has shown mutations in PIM1 (67%), MYD88 (44-59%), CD79b (26-67%), PRDM1 (44%), BTG2 (22%) and EZH2 (4%). [38][39][40][41][42][43] The immunoglobulin genes are clonally rearranged.…”
Section: Immunophenotypementioning
confidence: 99%
“…Immunophenotype, however, has not been shown to affect outcomes [16]. IVLBCL has been associated with complex karyotype and structural aberrations in chromosomes 1, 6q, and 18 in over 50% of IVLBCL cases [19].…”
Section: Discussionmentioning
confidence: 99%